2017
DOI: 10.1176/appi.ajp.2016.16060671
|View full text |Cite
|
Sign up to set email alerts
|

Association of Elevated Reward Prediction Error Response With Weight Gain in Adolescent Anorexia Nervosa

Abstract: Objective Anorexia nervosa is a psychiatric disorder of unknown etiology. Understanding associations between behavior and neurobiology is important in treatment development. Using a novel monetary reward task during functional magnetic resonance brain imaging, the authors tested how brain reward learning in adolescent anorexia nervosa changes with weight restoration. Method Female adolescents with anorexia nervosa (N=21; mean age, 15.2 years [SD=2.4]) underwent functional MRI (fMRI) before and after treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 39 publications
6
99
0
Order By: Relevance
“…Brain activation predicted weight gain during treatment, but short-term weight restoration was not associated with normalization of brain response. 75,76 Those studies suggested heightened dopamine-related brain response that does not easily normalize with weight recovery. 76 In summary, altered reward circuits in AN may be associated with altered learning and brain dopamine function, and traits such as sensitivity to punishment could be predisposing.…”
Section: Task-based Functional Mri Studies Reward Systemmentioning
confidence: 99%
“…Brain activation predicted weight gain during treatment, but short-term weight restoration was not associated with normalization of brain response. 75,76 Those studies suggested heightened dopamine-related brain response that does not easily normalize with weight recovery. 76 In summary, altered reward circuits in AN may be associated with altered learning and brain dopamine function, and traits such as sensitivity to punishment could be predisposing.…”
Section: Task-based Functional Mri Studies Reward Systemmentioning
confidence: 99%
“…Accumulating behavioral and neuroimaging evidence supports a neurobiologically‐based temperament that impacts the development and maintenance of AN—characterized by anxiety, reward insensitivity, perfectionism, altered interoceptive awareness, harm avoidance, and cognitive inflexibility (Fassino, Piero, Gramaglia & Abbate‐Daga, ; Harrison, O'Brien, Lopez, & Treasure, ; Lilenfeld, )—that is related to altered insula and fronto‐striatal neural circuit function (Berner et al, ; DeGuzman, Shott, Yang, Riederer, & Frank, ; Kerr et al, ; Oberndorfer et al, ; Wierenga et al, ). In addition to predating AN, mild to modest amounts of these traits often persist after recovery (Wagner et al, ), suggesting those who recover might do so by effectively managing these traits.…”
Section: Introductionmentioning
confidence: 99%
“…Neurobiological research from our group suggests that anorexia nervosa is associated with heightened responsiveness in brain reward circuits and this may be due to a hyper-sensitive dopamine system (DeGuzman, Shott, Yang, Riederer, & Frank, 2017; Frank, 2016b; Frank et al, 2012). The dopamine partial agonist aripiprazole is thought to down-regulate dopamine D2 receptor activity.…”
Section: Discussionmentioning
confidence: 99%